Opening up energy trading. - Maize, K. (IEEE spectrum)
In October 2001, Enron Corporation was doing well in the stock market. The future looked bright for Enron and its rivals in the intensely competitive business of selling electricity, natural gas, and financial products based on energy prices. A year later Enron had become a dirty word, embodying the corporate malfeasance that allowed executives to walk off with millions, while investors and employees saw their life savings go down the tubes. What happened? And what needs to be done to make electricity trading the transparent and honest business it must be if energy is to be produced and distributed to best economic effect? This paper outlines the fall of Enron, the complex California connection, credit risk and price transparency, and standardising power market structures. The paper also discusses whether energy trading has a future.